“Invalid busyness” behaviors of a few grassroots cadres: Evidence from normative explanation - Duan, Cheche; Zeng, Yan; Zhou, Yicheng; Li, Yingying (Frontiers in Psychology, 2022)
Effective grassroots governance is the foundation for the stability of state power, but the “invalid busyness” behavior of a few grassroots cadres has seriously deteriorated the local political ecology. In order to gain a deeper understanding of the mechanism of “invalid busyness” behavior of grassroots cadres, this paper, following the analysis of typological research and combined with publicly available data, classifies the “invalid busyness” behavior of grassroots cadres into eight types, including hedging and self-preservation, drifting with the stream, patchwork response, conforming old rulers, replacing targets, blame avoidance, trace doctrine, and self-waiver. It is found that the “invalid busyness” behavior of grassroots cadres is shaped by the risk society paradox, local management paradox, incentive intensity paradox and technical governance paradox, and the “invalid busyness” behavior of grassroots cadres needs to be corrected from the four-dimensional logic of incentive, restraint, deep care, and strict control. This study systematically describes the manifestation, causes and correction mechanism of the “invalid busyness” behavior of grassroots cadres, which enriches and expands the theoretical research on the performance behavior of grassroots cadres. Systematic review registration https://osf.io/h5wgj.